HUBUNGAN PROTEINURIA DAN ANGKA LEUKOSIT PADA IBU HAMIL DENGAN PREEKLAMPSIA BERAT DI RSUD PANEMBAHAN SENOPATI - Rismaya Salsabila Putri; Aji Bagus Widyantara; Lisa Wahyuningrum (Journal of Innovation Research and Knowledge, 2026)
Abstract: Maternal mortality remains a significant public health concern. Based on data from the 2020 Population Census Survey, maternal deaths accounted for approximately 33% of total mortality, with preeclampsia and eclampsia identified as the leading causes. This study was conducted to describe and analyze the relationship between the degree of proteinuria and leukocyte count in pregnant women diagnosed with severe preeclampsia at Panembahan Senopati Regional Hospital.A quantitative descriptive study with a cross-sectional design was employed. The sampling technique used was total sampling, including all medical records of urine protein and blood leukocyte examinations from pregnant women with severe preeclampsia who met the inclusion and exclusion criteria during the second semester of 2024. A total of 36 respondents were included in this study. Data were analyzed using descriptive statistics to illustrate the distribution of proteinuria levels and leukocyte counts. Furthermore, bivariate analysis was performed using the Spearman correlation test to evaluate the relationship between the two variables, with a significance level set at p < 0.05. The findings indicated that most participants presented with proteinuria levels of 2+ and 3+, along with elevated leukocyte counts (>10,000/mm³). However, no statistically significant correlation was found between the degree of proteinuria and leukocyte count (p = 0.241 ; p > 0.05). In conclusion, although both proteinuria and leukocyte levels are commonly elevated in cases of severe preeclampsia, their direct association could not be clearly established.